DIRETOR DE ESCOLA PÚBLICA: CATEGORIAS TEÓRICAS DE ANÁLISE NA PESQUISA SOBRE O SEU PAPEL - Miguel Henrique Russo; Margarete Bertolo Boccia (EccoS – Revista Científica)
The roles of school principals are analyzed from the theoretical categories used on an empiric research. The study confronted the functions that the State attributes to school principals and the perception that those on that position have about how this determines their practice. To build the analysis referential were used categories from the organizational theory and from the social Psychology, such as: function, role, stereotype, post, social identity, social rule and others. The focus of this text is centered on the clarification of the meanings attributed to the categories that support the analysis and interpretation of the research empiric data. Therefore, it became necessary to look in Literature for the senses attributed to the various categories that come up in the urge to comprehend the research object and clarify the senses they got in the study. An extract of the use of those categories is presented in the study conclusion.